Travail des enfants et droit à l' éducation au Burkina Faso - Joséphine Wouango (Les éditions de la Maison des sciences de l'Homme, 2011)
This article is about a particular case of children in working situation: children crushing the granite in the quarry of Pissy. Their working conditions are considered as dangerous by national and international legal texts. This article aims to grasp the experience of children who work in this frame in order to test the hypothesis according to which schooling would be an effective tool of struggle against child labour. The fieldwork reveals that child labour in the quarry is not only guided by economic aspects. The wish of the parents (and of some children and teenagers) to find another job for working children reopen the debate on "the right to work" for children.